Possíveis consequências da aquisição tardia da língua brasileira de sinais no desenvolvimento do acadêmico surdo - Vale, Thaynara de Souza (Universidade Federal do Tocantins, 2023)
In recent years there has been an increase in debates on the education of the deaf, and one of the questions that have been put on the agenda is how this process of including them in academic life occurs. Libras by itself is a visual language used by the Deaf Community, however, most deaf people complete basic education without knowing their first language, that is, Libras. Faced with situations, and difficulty observing the high percentage of deaf people who do not know sign language, this work portrays the cognitive barriers that deaf academics may face during their academic career, and for this purpose, it is a bibliographical, quantitative research, qualitative, and field. However, an interview was conducted with a deaf student to understand the mishaps she faces in her daily routine within the university, and to give greater strength and viability to the academic's speeches, some theoretical references were placed, such as OLIVEIRA(2020), QUADROS (2004), CHOMSKY(2022), VYGOTSKY(2002)...among others. This research was divided into four topics, the first will discuss the importance of language for human development, the second is a power relationship, and development process, the third linguistic reality of the deaf community, and finally the last topic is data analysis, this part will reveal the precariousness that the deaf academic go through daily with the slow process of linguistic development, which influences the cognitive of the deaf academic.